2017
DOI: 10.3389/fvets.2017.00159
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol Inhibits Equine Neutrophil Adhesion, Migration, and Respiratory Burst in an In Vitro Model of Inflammation

Abstract: In many equine inflammatory disease states, neutrophil activities, such as adhesion, migration, and reactive oxygen species (ROS) production become dysregulated. Dysregulated neutrophil activation causes tissue damage in horses with asthma, colitis, laminitis, and gastric glandular disease. Non-steroidal anti-inflammatory drugs do not adequately inhibit neutrophil inflammatory functions and can lead to dangerous adverse effects. Therefore, novel therapies that target mechanisms of neutrophil-mediated tissue da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 55 publications
2
19
1
1
Order By: Relevance
“…Other anti-inflammatory effects of misoprostol occur at much lower concentrations than those associated with TNFa production. In vitro equine studies report that misoprostol concentrations as low as 0.001 umol/L (approximately 0.38 ng/mL) inhibit LPS-induced equine neutrophil respiratory burst [36], which is much more similar to the concentrations obtained in this study. Therefore, it is possible that misoprostol will affect leucocyte function directly and indirectly through its actions on other cell types in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…Other anti-inflammatory effects of misoprostol occur at much lower concentrations than those associated with TNFa production. In vitro equine studies report that misoprostol concentrations as low as 0.001 umol/L (approximately 0.38 ng/mL) inhibit LPS-induced equine neutrophil respiratory burst [36], which is much more similar to the concentrations obtained in this study. Therefore, it is possible that misoprostol will affect leucocyte function directly and indirectly through its actions on other cell types in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…Misoprostol is a prostaglandin E 1 analogue that is licensed for the treatment of refractory glandular disease in human patients. It has a number of effects on the stomach in other species which include doserelated inhibition of gastric acid and pepsin production and secretion, enhancement of mucosal resistance to injury, promotion of gastric mucosal proliferation in humans and dogs [31], increases gastric mucosal blood flow and has anti-inflammatory properties [32,33]. One experimental study in horses demonstrated that misoprostol effectively suppresses acid production and secretion in the horse and, when compared with oral omeprazole, this effect was shown to be longer in duration [34].…”
Section: Introductionmentioning
confidence: 99%
“…Misoprostol is a prostaglandin analogue and an increasingly popular treatment for EGGD that has multiple mechanisms of action that may be of benefit. Misoprostol suppresses acid production (Sangiah et al, 1989) and inhibits neutrophilic inflammation (Martin et al, 2017) and is therefore a logical treatment for EGGD. However, there is limited evidence of its efficacy.…”
Section: Misoprostolmentioning
confidence: 99%